Acropora formosa Development in Various Depths at Pramuka Island, Seribu Island National Park - Irhas, Muhammad; Harahap, Syawaludin A; Sunarto, Sunarto; Ismail, Mochamad Rudyansyah; Faizal, Ibnu (Marine Science Department Diponegoro University, 2025)
Coral transplantation is a proven method for restoring degraded marine ecosystems affected by environmental changes and human activities. This study investigates how depth influences the growth and survival of Acropora formosa using the RakSagon structure at Gosong Pramuka Island, Seribu Islands. RakSagon is a hexagonal dome frame made of 10 mm iron, coated with a resin-catalyst mixture, and designed with two tiers to support coral fragment attachment. The observation spanned 378 days and was divided into three monitoring periods (t0–t3) with varying intervals. The study analyzed growth, survival, and effectiveness at depths of 3, 5, and 7 m. Additionally, the ratio between coral length and width (0.38–1.08) was measured to identify horizontal or vertical growth tendencies. The highest growth occurred at 7 m, averaging 1.41–1.74 cm.mo-1, while the lowest was at 3 m (0.68–0.99 cm.mo-1). Growth varied between observation periods, with the second interval showing the most notable increase. Fragment survival was evaluated using the Survival Rate (SR) and Mortality Index (MI); the MI value of 0.305 indicated moderate mortality, with a 69% success rate (25 of 36 fragments survived). A one-way ANOVA test revealed a significant difference in growth rates among the depths (P= 0.004), confirming that depth plays a crucial role in transplantation outcomes. The findings suggest that a depth of 7 m offers optimal conditions for coral growth and survival, providing valuable insights for future reef restoration programs and stakeholder initiatives.